Irradiation-induced toughening of calcium aluminoborosilicate glasses. (June 2022) - Ren, Xiangting; Du, Tao; Peng, Haibo; Jensen, Lars R.; Biscio, Christophe A.N.; Fajstrup, Lisbeth; Bauchy, Mathieu; Smedskjaer, Morten M.
Abstract: Methods to improve the fracture toughness and strength of glassy materials are increasingly important for a variety of applications that remain limited by the restrictions of brittleness and surface defect propensity. Here, we report on the enhancement of glass mechanical performance through a combination of a tailored chemistry and irradiation post-treatment. Specifically, we show through both experiments and atomistic simulations that the defect (crack) initiation resistance as well as the fracture toughness of selected calcium aluminoborosilicate glasses can be significantly improved (by more than 400% in some cases) through heavy ion irradiation. The ion irradiation process reorganizes the borate subnetwork through a partial transformation of tetrahedral to trigonal boron units, which in turn also modifies the glass at longer lengths scales, such as through a coarsening in the distribution of loop structures. The improvement in both the resistance to crack formation and crack growth is ascribed to the modification of the medium-range glass structure as well as the less rigid network structure upon irradiation with coordination defects that act as local reservoirs of plasticity by allowing more bond switching activities to dissipate mechanical energy upon deformation. This work therefore highlights a new pathway to develop damage-resistant glass materials. Graphical Abstract: ga1 Highlights: Heavy ion irradiation modifies the structure and mechanical properties of calcium aluminoborosilicate glasses. Crack initiation resistance and fracture toughness are improved simultaneously. Structural origin of toughening is investigated through atomistic simulations and topological data analysis. Changes in medium-range structure and coordination defects allow for more bond switching activities and dissipation of mechanical energy.